Identifikasi Penutupan dan Kondisi Fisik Area Rencana Pembangunan Lahan Peternakan PT. Asiabeef Biofarm Indonesia di Desa Lailanjang, Kecamatan Rindi, Kabupaten Sumba Timur, Propinsi Nusa Tenggara Timur. - Bernandus Bernandus; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted to determine the biophysical aspects and their impact on the community around the livestock land development planned area in Lailanjang village, Rindi district, East Sumba regency, East Nusa Tenggara province. this type of research is descriptive with qualitative methods with the data sources used in this study. The study data is divided into two types of data, primary data and secondary data. Primary data is data obtained directly from the field through measurements, observations, calculations, notes and interviews with related parties related to the object being studied. Primary data obtained include stand data (diameter and height), area based on sample plots made and socio-economic data and community perceptions obtained through interviews. The results of the field study show that the location of the livestock land development planned area in Lailanjang village, Rindi district, East Sumba regency, East Nusa Tenggara province which is indicated to be included in the Indicative Map of Delaying the Granting of New Permits for forest use. The potential of natural resources available in the area of the livestock land development planned area is generally not too large, considering that the condition of the land around the planned livestock land development area is classified as unfavorable for agricultural development, the location has been used as a traditional grazing area by the local community. Vegetation/coverage in the area of the livestock land development planned area is dominated by Grass (Imperata cylindrica Raeusch), (Cyperus rotundus) and and a few Gum lac (Schleichera oleosa) trees in steep areas